Musical form and transformation: Four analytic essays - Lewin, David (New York Oxford university press, 2007)
Distinguished music theorist and composer David Lewin (1933-2003) applies the conceptual framework he developed in his earlier, innovative Generalized Musical Intervals and Transformations to the varied repertoire of the twentieth century in this stimulating and illustrative book. Analyzing the diverse compositions of four canonical composers--Simbolo from Dallapiccola's Quaderno musicale di Annalibera ; Stockhausen's Klavierstuck III ; Webern's Op. 10, No. 4; and Debussy's Feux d'articifice --Lewin brings forth structures which he calls "transformational networks" to reveal interesting and suggestive aspects of the music. In this complementary work, Lewin stimulates thought about the general methodology of musical analysis and issues of large-scale form as they relate to transformational analytic structuring. Musical Form and Transformation , first published in 1993 by Yale University Press, was the recipient of an ASCAP Deems Taylor Award.